1971
DOI: 10.1203/00006450-197112000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Adult Erythrocyte Lipids during In Vivo Fetal Circulation

Abstract: Pediat. Res. 5/ 683-690 (1971) ExtractThe effects on membrane lipid composition of chronic in vivo exposure of adult cells to a fetal plasma environment were studied in eight infants who received repeated intrauterine transfusions for erythroblastosis fetalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Plasma phospholipid analysis was performed on 7 of the samples from the 6-14 year age group and revealed that phosphatidyl choline comprises 67.9% and sphingomyelin 16.5% of the total phospholipid. Previous studies from our laboratory revealed rather similar values for cord blood (phosphatidyl choline = 67.6%, sphingomyelin 17.9%) [19]. Thus the S:PC ratio in plasma in the 6-14 year group is 0.24 whereas that in cord blood is 0.26.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Plasma phospholipid analysis was performed on 7 of the samples from the 6-14 year age group and revealed that phosphatidyl choline comprises 67.9% and sphingomyelin 16.5% of the total phospholipid. Previous studies from our laboratory revealed rather similar values for cord blood (phosphatidyl choline = 67.6%, sphingomyelin 17.9%) [19]. Thus the S:PC ratio in plasma in the 6-14 year group is 0.24 whereas that in cord blood is 0.26.…”
Section: Discussionsupporting
confidence: 53%
“…Since cell surface area is difficult to determine accurately, previous discussions have utilized the association between lipid content of erythrocytes and volume of erythrocytes to express this relation [16,18,19]. Thus, the normal newborn erythroeyte has 5.38 x 10-10 mg lipid/100 ju, 3 while the normal adult ranges from 5.07 to 5.14 X 10-10 mg lipid/100 ^ [19]. Utilizing such calculations, it can be shown that the variations in lipid content of erythrocytes noted in this study largely reflect the variations in mean corpuscular volume of erythrocytes in the respective age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phospholipid and phospholipid fatty acid composition of reticulocytes is similar to that of older cells, however [26]. Cord bloods containing large numbers of nucleated erythrocytes and reticulocytes (obtained from erythroblastotic infants) give values for total lipid, lipid P, and cholesterol significantly lower than those from infants with birth weights ranging from 200 to 1,200 g (total lipid = 7.11 X 10-" mg/cell; P = 1.74 X 10-" mg/cell; cholesterol = 1.86 x 10-10 mg/cell) [17]. The phospholipid and phospholipid fatty acid composition of these young cell-rich cord bloods does not differ from those of normal term infants [17].…”
Section: Discussionmentioning
confidence: 99%